An Econometric Analysis of Unemployment Insurance Benefit Adequacy - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 1990)
Traditionally studies of unemployment insurance benefit adequacy have relied on an expenditure survey. This is expensive, yields small samples, and presumes that the analyst knows which categories of expenditure are necessary. This paper uses an existing large data set, and an agnostic approach. Labor supply are equations are estimated on PSID data using an estimator which accounts for rationing in the labor market. The results are used to compute labor market constraint compensation for comparison to payments under UI systems of representative states. The results suggest that payments which meet the accepted standard of adequacy would usually slightly overcompensate individuals.
Keywords: J0; J6; 330; unemployment; insurance; adequacy; benefits; O'Leary